CONOMIC EXPANSION AND MAPUCHE CONFLICT. THE ARAUCANIA, 1900-1940 - Pinto Rodríguez, Jorge (Revista de Historia Social y de las Mentalidades, 2011)
This article examines the economic expansion which  occurred in the Araucanía  during the first half of the Twentieth Century and  its impact on Mapuche society. The  founding of cities, new economic circuits generated inside the region, and the new  connections of the regional economy with external m arkets encouraged an economic  expansion which favored the Mapuche communities who saw the new markets as a place to  display their products. This stage (1890-1920/30)  corresponds to the successful connection  of the region to the State; however, there were als o a series of abuses against the indigenous  people, the most serious of which was land robbery. This successful phase was followed by  some loss in the economic dynamics which affected s mall and medium farmers especially  in the 1930s. Mapuche communities felt the effects of the situation, and some of their  members had to migrate to Concepción, Santiago or V alparaíso in search of better horizons.  Therefore, it was a time of lights and shades for t he region and the Mapuche people. It was  not possible to sustain economic expansion, and the abuses against the Mapuche people  weakened their defenses to face the economic contra ctions which took place after the  1930s.
Keywords: Araucanía,; 20 th Century; Mapuche people